The little deflections of the previously intense ideal plastic beams with the regional moments and load distribution - I A Monakhov; U K Basov (RUDN Journal of Engineering Research, 2015)
In the work up the technique of the decision of problems about the little deflections of beams from ideal heard-plastic material, with various kinds of fastening, for want of action of the asymmetrically distributed loads with allowance for of preliminary stretching-compression is developed. The developed technique is applied for research of the strained-deformed condition of beams, and also for calculation of a deflection of beams with allowance for of geometrical nonlinearity.